2022
DOI: 10.1186/s43141-022-00336-1
|View full text |Cite
|
Sign up to set email alerts
|

A small molecule, C24H17ClN4O2S, inhibits the function of the type III secretion system in Salmonella Typhimurium

Abstract: Background Salmonella enterica serovar Typhimurium (S. Typhimurium) causes gastroenteritis and diarrhea in humans and food-producing animals. The type III secretion system (T3SS) has been known to be a potent virulence mechanism by injecting effector proteins into the cytosol of host cells. S. Typhimurium encodes two T3SSs by Salmonella pathogenicity islands 1 and 2. Previous studies showed that T3SS shared a potent virulence mechanism and molecular structure among several gram-negative bacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
0
1
0
Order By: Relevance
“…A similar development strategy could be applied to other human pathogens that contain T3SSs, including enteropathogenic E. coli , S. flexneri , S. typhimurium , and Burkholderia mallei/pseudomallei species [ 125 ]. Recently, Boonyom et al [ 127 ] found that compound 25 interdicted the secretion of the effector protein SPI-1 of Salmonella T3SS at a concentration of 100 μM. The compound also attenuated the bacterial invasion of epithelial cells.…”
Section: Synthesized Inhibitors Of T3sssmentioning
confidence: 99%
“…A similar development strategy could be applied to other human pathogens that contain T3SSs, including enteropathogenic E. coli , S. flexneri , S. typhimurium , and Burkholderia mallei/pseudomallei species [ 125 ]. Recently, Boonyom et al [ 127 ] found that compound 25 interdicted the secretion of the effector protein SPI-1 of Salmonella T3SS at a concentration of 100 μM. The compound also attenuated the bacterial invasion of epithelial cells.…”
Section: Synthesized Inhibitors Of T3sssmentioning
confidence: 99%
“…In addition, inhibition of T3SS ATPase avoids the risk of cross-reaction between T3SS ATPase inhibitors and human ATPase enzymes because bacterial ATPase and human ATPase share less than 25% of their sequences and their active sites are structurally different 5 . Though there are many existing inhibitors of Salmonella T3SS, none have been shown to target the InvC protein vital for combating antibacterial resistance 20,21,22,23,24 .…”
Section: Introductionmentioning
confidence: 99%